If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 2y + -10x Reorder the terms: 11 = -10x + 2y Solving 11 = -10x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 11 + 10x = -10x + 10x + 2y Combine like terms: -10x + 10x = 0 11 + 10x = 0 + 2y 11 + 10x = 2y Add '-11' to each side of the equation. 11 + -11 + 10x = -11 + 2y Combine like terms: 11 + -11 = 0 0 + 10x = -11 + 2y 10x = -11 + 2y Divide each side by '10'. x = -1.1 + 0.2y Simplifying x = -1.1 + 0.2y
| -5(w+1)-w-6=-6(w+5)+19 | | 36x^9+13=0 | | 1/8m-1/4=3/4 | | -n/7-8+3n= | | 3x+7=8x+17 | | 2(6x+4)=4x+16 | | 8xy-6y+5=0 | | 3-2(x+6)-8x=180-4x | | 29=2y+15 | | w/4=2 | | 8x-(6x+5)=3x-43 | | -3x^2y^2+7xy+1=0 | | -(1/5)^0 | | 205=2x-7 | | b-x/-1 | | 2(4x+6)=9x-3 | | q^(8/3)*q^(-5/3) | | 12/h-9+4h= | | 18=9/10(x-1 | | U/3-16=21 | | 10(v+4)-2v=4(2v+2)-16 | | p=2(12)+2(54) | | 92.7*14.2= | | q^3/3 | | 0=-2n | | 5(3x-6)-3(x+3)-15x= | | -8(v+4)+3v+5=5v+7 | | (-8x^3/y^-8)^(2/3) | | 56=6(X) | | 5-(t+3)=-1+2(t-5) | | 5w-3(4x-2w)+3x= | | A=1/2(4.5*h) |